Free radical scavenging, α-amylase, α-glucosidase, and lipase inhibitory activities of metabolites from strawberry kombucha: Molecular docking and in vitro studies - Adriyan Pramono; William Ben Gunawan; Fahrul Nurkolis; Darmawan Alisaputra; Gilbert Ansell Limen; Muhammad Subhan Alfaqih; Martha Ardiaria (Pensoft Publishers, 2024)
Obesity, a global issue, is linked to cardiometabolic syndrome. Dietary modification is one of the recommended modes for managing cardiometabolic syndrome. Strawberries, a functional food, and kombucha, a fermented tea beverage, have gained attention for their health benefits. This study investigated the bioactive components of strawberry kombucha drink (SKD) and their effects on antioxidant activities and improving metabolic disorder markers. An in vitro experiment was performed to determine the effect of SKD on enzymatic parameters: lipase, α-glucosidase, and α-amylase activities. In addition, antioxidant activity using the DPPH method and quantification of the radical scavenging activity were also measured. Furthermore, untargeted metabolomic profiling of SKD and molecular docking simulation were conducted. The findings suggest that SKD, rich in secondary metabolites, can inhibit lipase, α-glucosidase, and α-amylase activities. It demonstrated in vitro anti-obesity, anti-diabetic, and antioxidant properties, potentially reducing metabolic and inflammatory issues. Thus, SKD could be a therapeutic beverage to alter metabolic issues associated with obesity. Nevertheless, further preclinical study is warranted to determine SKD's potential in vivo.